Reproductive characteristics of Ethiopian highland sheep. II. Genetic parameters of semen characteristics and their relationships with testicular measurements in ram lambs - Rege, J.E.O.; Toe, F.; Mukasa-Mugerwa, E.; Tembely, S.; Anindo, D.O.; Baker, R.L.; Lahlou-Kassi, A. (Elsevier, 2000)
A study was conducted to investigate the effect of season on, and to estimate heritabilities of, and genetic correlations among, semen and spermatozoa characteristics and the relationship of these characteristics with measures of testicular or scrotal size in 6-, 9- and 12-month old ram lambs of Menz and Horro sheep breeds indigenous to Ethiopian highlands. A total of 278 ram lambs with substantial pedigree information were involved in the study. There was improvement in all semen and spermatozoa traits with age, the means at 12 months being consistently superior to values at 6 and 9 months of age. There were no significant breed differences in any of the traits studied, except semen volume at 9 months (0.67, S.E. 0.07 for Horro versus 0.39, S.E. 0.05 ml for Menz) and proportion of dead spermatozoa at 12 months (0.18, S.E. 0.03 versus 0.23, S.E. 0.02, respectively). Season was significant (p<0.05) for most of the traits studied, and differences were attributed primarily to nutrition. Semen collected in the wet season had higher spermatozoa concentration while samples collected in the dry season had higher proportion of abnormalities. After correcting for differences in total spermatozoa abnormalities, the wet season (of collection) had the highest spermatozoa output (volume X concentration) in 12-month old ram lambs. Heritability estimates varied substantially in magnitude, ranging from zero to over 0.4. Traits with non-trivial heritability estimates were mass motility at 9 months (0.32, S.E. 0.11), individual motility at 9 months (0.32, S.E. 0.12) and at 12 months (0.16, S.E. 0.12) and proportion of abnormal spermatozoa at 9 months (0.35, S.E. 0.13). Genetic correlations among semen and spermatozoa characteristics, as well as correlations with testicular measurements, were medium to high and generally favourable, but were associated with large standard errors. The genetic correlations of scrotal circumference with semen volume (0.55, S.E. 0.11), mass motility (0.62, S.E. 0.20), individual motility (0.54, S.E. 0.12), concentration (0.25, S.E. 0.04) and proportion of abnormal spermatozoa (-075, S.E. 0.24) in 12-month old rams indicated that selection based on this trait, which is highly heritable and easy to measure and can be measured early in life, should have appreciable favourable correlated response in semen quality and spermatozoa production.